2007
DOI: 10.4278/0890-1171-21.4s.317
|View full text |Cite
|
Sign up to set email alerts
|

Green Neighborhoods, Food Retail and Childhood Overweight: Differences by Population Density

Abstract: This research suggests that aspects of the built environment are determinants of child weight status, ostensibly by influencing physical activity and dietary behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
183
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(199 citation statements)
references
References 44 publications
10
183
3
Order By: Relevance
“…For example, Liu and colleagues reported an association between vegetation and youth body weight that was stronger in more densely populated areas. 59 We explored potential interactions between the neighborhood environment characteristics and season of physical activity measurement. In addition, examining associations within distinct populations and settings, such as our population of young children in a lowincome urban environment, can add to a broader understanding of effect modification across the published literature.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Liu and colleagues reported an association between vegetation and youth body weight that was stronger in more densely populated areas. 59 We explored potential interactions between the neighborhood environment characteristics and season of physical activity measurement. In addition, examining associations within distinct populations and settings, such as our population of young children in a lowincome urban environment, can add to a broader understanding of effect modification across the published literature.…”
Section: Discussionmentioning
confidence: 99%
“…Relationship between food environment and individual food behaviour Among the twenty-nine articles reviewed, eleven (38 %) analysed associations between food environment and individual food behaviours (22)(23)(24)(25)(26) , weight status (27)(28)(29)(30)(31) or perceived availability of healthy food (32) . In those studies, the addresses of respondents were geocoded and used as references for GIS analyses.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…In those studies, the addresses of respondents were geocoded and used as references for GIS analyses. Four studies were performed on children or teenagers (24,27,28,31) , and the others on adult populations (one specifically concerned pregnant women (33) ). The outcomes of selected studies were consumption of fruits and vegetables (22)(23)(24)28) , perception of availability of healthy food (32) , dietary patterns (26,33) and prevalence of overweight or obesity (27,(29)(30)(31) .…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Some found no association between children's weight gain and differential exposure to food outlets [74][75][76][77][78]. Others found that increased fast food access [79][80][81] or a higher ratio of fast food to full-service restaurants [81] was associated with a higher BMI. Unlike the extant literature, our results suggest that fast food in general has no impact on rural children's BMI percentile.…”
Section: Discussionmentioning
confidence: 99%